Efek proteksi hipoksia hipobarik intermiten pada otak tikus: Analisis konsentrasi Caspase-3, Neutrophin-3, karbonil dan SOD - Ninik Mudjihartini; Defli Yuandika Ruso; Wawan Mulyawan; Atikah Chalida Barasila; Yulhasri (Atma Jaya Catholic University of Indonesia, 2026)
Introduction: The brain is the largest energy-consuming organ in the body and is highly vulnerable to damage under hypoxic conditions. However, certain periods of hypoxia can be tolerated and provide protective effects. This study aimed to investigate the protective effects of intermittent hypobaric hypoxia (IHH) on the expression of caspase-3, neurotrophin-3, carbonyl, and superoxide dismutase (SOD) levels in rat brain tissues. Methods: A total of 25 male Wistar rats were divided into five groups: a control group (normoxic conditions) and four treatment groups exposed to hypobaric hypoxia in a chamber simulating 25,000 feet altitude for 5 minutes at intervals of 7 days for each exposure. Group 1 was exposed to a one-time hypoxia condition (IHH 1), group 2 was exposed two times (IHH 2), group 3 was exposed three times (IHH 3), and group four were exposed four times (IHH 4). Results: Caspase-3 levels significantly decreased in the treatment groups compared to the control group (p<0.05), indicating a positive response to IHH. In contrast, neurotrophin-3 and carbonyl levels showed no significant changes across the groups, maintaining a stable trend. Additionally, a significant increase in SOD levels was observed between group 1 and group 3 (p<0.05), suggesting enhanced antioxidant defense with repeated IHH exposure. Conclusion: Intermittent hypobaric hypoxia can suggest a protective effect against hypoxic damage by suppressing caspase-3 expression. Repeated IHH exposure enhances antioxidant defense by elevating SOD levels. In contrast, neurotrophin-3 and carbonyl levels remain unchanged, suggesting these markers are unresponsive to short-term IHH.